Design of dispersant structures for preparing highly concentrated one-dimensional inorganic molecular chains from V2Se9 crystals - Chae, Sudong; Siddiqa, Akhtar J.; Kim, Bum Jun; Oh, Seungbae; Choi, Kyung Hwan; Kim, Hyo Yeol; Lee, Keun Ho; Yu, Hak Ki; Choi, Jae Young (Chemical Communications, 2018)
We studied dispersants for exfoliating bulk V2Se9 into one dimensional chain units. V2Se9, with a negative zeta potential of −30.1 mV, was acidic and strongly anchored with the amine head of octadecylamine by charge transfer reaction. The steric hindrance by the octadecyl tail promoted the dispersion of V2Se9 to the nano level.